2018
DOI: 10.14309/crj.2018.94
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pancreatitis with Spontaneously Disappearing Calcifications

Abstract: Pancreatic calcifications, exocrine insufficiency, and endocrine insufficiency are hallmarks of chronic pancreatitis, and their prevalence increases with the duration of disease. We present a case of chronic pancreatitis in which a dramatic and spontaneous decrease in the burden of both parenchymal and intraductal calcifications was noted during longitudinal follow-up. We discuss the possible reasons for spontaneously vanishing calcifications, an entity rarely described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Interestingly, recent observations imply that pancreatic calcifications may even spontaneously dissolve over time, although this is probably a rare event 38 .…”
Section: Risk Factors For Pancreatic Calcificationsmentioning
confidence: 99%
“…Interestingly, recent observations imply that pancreatic calcifications may even spontaneously dissolve over time, although this is probably a rare event 38 .…”
Section: Risk Factors For Pancreatic Calcificationsmentioning
confidence: 99%
“…Pancreatic duct stone autolysis in the natural history of CP has been recorded in some cases. 17 It was reported that approximately 30% of CP cases presented a marked reduction of calcium deposition in the later stages of CP, and PDS autolysis is a frequent pathological process. 17 , 18 The reason behind this may be that drinking and smoking cessation partially restore the secretory functions of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“… 17 It was reported that approximately 30% of CP cases presented a marked reduction of calcium deposition in the later stages of CP, and PDS autolysis is a frequent pathological process. 17 , 18 The reason behind this may be that drinking and smoking cessation partially restore the secretory functions of the pancreas. The dissolution of PDS in this research is mainly owed to the effect of ECGG treatment because the dissolution rate of the ECGG group was significantly higher than that of the CON group ( P = .002; Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of any serial investigations of pancreatic duct morphology over time to compare this finding with. Anecdotal evidence suggests that pancreatic duct obstruction may resolve spontaneously ( 32 ). However, according to our observations, this is a relatively rare event, and as such, pancreatic duct morphology does not change in most medically managed patients with CP.…”
Section: Discussionmentioning
confidence: 99%